Recurrent hypoglycaemia in a diabetic patient: the unexpected diagnosis - Ooi, Poh Siang; Draman, Nani; Mustaffa, Nazri; Jamani, Nurjasmine Aida (Kulliyyah of Medicine, International Islamic University Malaysia, 2023)
Hypoglycaemia is a common complication seen in diabetic patients receiving insulin. However, insulin is not the risk factor for hypoglycaemia attack as patient with underlying liver problem is also at risk. Thus, as an attending physician, a high index of suspicion is required in dealing with hypoglycaemia patient. We report a 60-year-old woman with underlying diabetes mellitus who presented with recurrent hypoglycaemic episodes and noted to have multiple benign liver cysts that progressed into hepatic failure secondary to hepatocellular carcinoma.